Respostas

2014-08-11T19:15:50-03:00
Mais de 45 de 35 468 ddde 123 fty 
A melhor resposta!
2014-08-11T19:18:33-03:00
F(x) = 3x + 5

a)
f(1) = 3.1 + 5 = 3 + 5 = 8
f(-2) = 3(-2) + 5 = -6 + 5 = -1
f(-3) = 3(-3) + 5 = -9 + 5 = -4

f(1) + f(-2) + f(-3) = 8 + (-1) + (-4) = 8 - 5 = 3

b)
f(5) = 3.5 + 5 = 15 + 5 = 20
f(10) = 3.10 + 5 = 30 + 5 = 35
f(-2) = 3(-2) + 5 = -6 + 5 = -1

f(5) + f(10) - f(-2) = 20 + 35 - (-1) = 55 + 1 = 56

c)
f(6) = 3.6 + 5 = 18 + 5 = 23
f(8) = 3.8 + 5 = 24 + 5 = 29
f(0) = 3.0 + 5 = 0
 

f(6) - f(8) - f(0) = 23 - 29 - 0 = -6

2 4 2